“Nursery bays and hidden rays”: First insights into long-term monitoring of Bull Rays (Aetomylaeus bovinus) within the Maltese Archipelago - Matthews, Charlie; Caruso, Christian; Kell, Charlotte; Babbs, Sophie; Parreira do Amaral, Thaís; Ducker, Beth; Nowell, Greg; Solleliet-Ferreira, Silvio (Frontiers in Marine Science, 2025)
This study constitutes a novel quantitative assessment of Aetomylaeus bovinus distribution and demographics within the Maltese archipelago (MA, Central Mediterranean). According to the IUCN red list, A. bovinus is critically endangered, both globally and in the Mediterranean. Therefore, a comprehensive understanding of its ecological attributes and behaviors is necessary for adequate conservation measures. Despite their crucial role in providing ecosystem services, information on batoids around the MA remains limited, raising concerns over their increasing population decline and extinction risk. During this fourteen-year-long study (2011-2024), photo-identification data were collected by members of Sharklab-Malta in conjunction with the Fly With Bull Rays (FWBR) program in order to identify site fidelity, population structure and temporal-spatial behavioral patterns of local A. bovinus. Seasonal patterns and relative abundance were also ascertained. A total of 859 surveys were conducted around the MA, with a total of 407 sightings of A. bovinus and the identification of 135 individuals. Approximately 44.8% of identified individuals were re-sighted at least once following initial observations, with multiple individuals showing high re-sighting rates across lengthy temporal periods and indicating site fidelity. Certain key areas in the NW, NE and E of Malta represent the greatest abundance of A. bovinus in the MA. The population is dominated by younger individuals, defined by disc width, with 97.7% of sightings consisting of young of the year to sub-adults. These data, in tandem with site fidelity, higher abundances of juveniles in these key areas and consistent use of these areas over the fourteen-year study period suggest that areas of the MA support a nursery function for A. bovinus. Anthropogenic stressors such as high touristic pressure, unregulated fishing and climate change are likely to impact key areas, posing a need for targeted conservation measures.